Monosialoganglioside protected ischemic rat hippocampal slices through stabilizing expression of N-methyl-D-aspartate receptor subunit - LIU Jian-ren; DING Mei-ping; WEI Er-qing; HUANG Jian-zheng; SONG Ying; DING Qiang; GE Qiu-fu (Acta Pharmacologica Sinica, 2016)
AIM: To determine direct protective effect of monosialoganglioside (GM1) on hippocampal slices after oxygen-glucose deprivation and reperfusion (OGD/RP), and investigate the influence on the expression of N-methyl-D-aspartate receptor subunit 1 (NMDAR1) in those hippocampal slices. METHODS: Injury of hippocampal slices and protective effects of GM1 were detected by 2,3,5-triphenyltetrazolium chloride (TTC) staining, toluidine blue staining, and transmission electron microscopy of rat hippocampal slices. Expression of NMDAR1 was detected by Western blot. RESULTS: (1) GM1 at 1.0 micromol/L was the most effective concentration to preserve the TTC staining of the hippocampal slices after OGD/RP (P